A HIGHER INCIDENCE OF RELAPSE FOR ACUTE LYMPHOCYTIC LEUKEMIA TREATED WITH ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION CONDITIONED WITH BU-CY2 REGIMEN - 朱康儿 钟隽 张涛 曾慧兰 (Chinese journal of cancer research, 2003)
Objective: To analyze long-term outcome in sixty leukemia patients received allogeneic hematopoietic stem cell transplantation (allo-HSCT) following busulfan and cyclophosphamide (BU-CY2) between 1994 and 2000.Methods: BU-CY2 was used as the conditioning regimen and allo-HSCT was performed for all patients. All the patients were followed-up until August 2001 or death. The leukemia-free survival, relapse and transplant-related mortality were discussed. Results: All 60 patients had sustained engraftment. Acute GVHD occurred in 22 out of 60 patients (36.7%), and the incidence of acute GVHD was 48% in the patients with CML, 30% in AML and 26.7% in ALL. 38 patients are still alive in continuous remission with a median follow-up of 30 months (range 12-84) and 22 patients have died. The main causes of death were acute GVHD in 3 patients, CMV-IP in 7 patients and relapse in 11 patients,the remaining one died of pulmonary infection. Among 11 patients who died of relapse, 8 patients with ALL relapsed in the early stage post transplant (8115, 53.3%), relapse was observed in the remaining 3 patients with AML, and however, no relapse was observed in CML. The probability of disease-free survival at 3 years for CML. AML and ALL patients was 80%, 70% and 26.7%, respectively.Conclusion: This results suggests that BU-CY2 is an effective conditioning regimen in patients with AML and CML, resulting in a low relapse rate and high long-term survival rate, but not as effective in patients with ALL, with a higher incidence of relapse and therefore, not recommended for ALL patients.